Four new species of Enochrus Thomson (Coleoptera: Hydrophilidae) from southern China - Mai, Zu-Qi; Jia, Feng-Long (Zootaxa, 2024)
Four new species of the water scavenger beetle genus Enochrus Thomson, 1859 are described from China. Among the new species, Enochrus hani sp. nov. from Yunnan and E. tathagatus sp. nov. from Xizang are very similar to E. laoticus Hebauer, 2005 and E. niisatoi Minoshima, 2017 in aedeagus and external morphology. E. imprimedius sp. nov. from Guizhou is similar to E. liangi Jia & Zhao, 2007 and E. japonicus sharp, 1873 in general form and colour. E. strangulatus sp. nov. from Guangxi is similar to E. laoticus Hebauer, 2005, but elytra with five longitudinal rows of punctures and a marginal series. Species diagnoses, illustrations and a distribution map of the new species are provided.